Professional Learning Communities Assessment: Adaptation, Internal Validity, and Multidimensional Model Testing in Turkish Context - (:unkn) unknown (EDAM, 2017)
The main purpose of this study is to adapt and validate the Professional Learning Communities Assessment Revised (PLCA-R) by Olivier, Hipp, and Huffman within the context of Turkish schools. The instrument was translated and adapted to administer to teachers in Turkey. Internal structure of the Turkish version of PLCA-R was investigated by using confirmatory factor analysis (CFA). After examining four alternative CFA models that have the potential to validate the internal structure of Turkish version of PLCA-R, we decided to retain the six-factor model with correlated residuals because it best explained the perception of teachers in Turkey according to a variety of criteria. After completing the adaptation study, for elementary teachers, we also modeled the relationship between individual, interpersonal, and organizational dimensions of professional learning communities accounting for teacher characteristics and school contextual factors. We found that organizational capacity is a statistically significant predictor for interpersonal capacities. However, professional development, as a personal capacity, was not a statistically significant mediator of this relationship in the model. We provided discussion on the dimensionality, methodological issues, and appropriate use of the translated instrument as well as on how our tested model can be interpreted for directions to future studies.
Keywords: Professional learning communities; Communities of practice; Professional development; Multidimension; Internal Structure; CONFIRMATORY FACTOR-ANALYSIS; FIT INDEXES